PENGARUH UNDANG-UNDANG KEPAILITAN DAN UNDANG-UNDANG HAK TANGGUNGAN TERHADAP KEDUDUKAN KREDITUR PEMEGANG HAK TANGGUNGAN APABILA DEBITUR PAILIT - Arya Aditya Pramana, Putu; Wairocana, I Gusti Ngurah (Kertha Semaya : Journal Ilmu Hukum, 2013)
In the Bankruptcy Act and the Mortgage Act lies a conflict of norms, which in both of these laws regulate the same mattersregarding the authority in the execution of creditor’s mortgageobjects if the debtor is bankrupt. Mortgage Act putting dependents position holders of mortgage lenders as a preferred lender with authority to execute the object's own freedom mortgages, whereas the Bankruptcy Act notch lenders mortgage holders preferred but limited execution rights. Thus, it can be drawn a conclusion that the decision of the bankruptcy court imposed not result in the destruction of the rights of dependents. Creditors mortgage holder retains the right to execute the object's own preference mortgages under their control. However, the execution time of the suspension of the right of mortgage guarantees a maximum of 90 (ninety) days from the decision rendered by the bankruptcy court. In writing this paper the authors use this type of normative juridical research.
Keywords: Creditor, Debtor, Bankruptcy, Mortgage